THE EFFECT OF IMPLEMENTING SEMESTER CREDIT SYSTEM (SKS) COURSES ON SYMBOLIC INTERACTION OF SENIOR HIGH SCHOOL STUDENTS IN CIREBON - Ulfa Latifa; Surya Amami Pramuditya; Peti Indrasari; Siti Nuarini (Cirebon International Conference on Education and Economics Proceeding, 2024)
The implementation of the 2013 curriculum requires students to be creative, innovative, and fast and responsive. The implementation of the 2013 curriculum brings a new method of learning, namely the Semester Credit System (SKS) in high schools. Learning using SKS is one innovative alternative to improving the quality of learning. This SKS program provides varied learning and flexible learning time management adjusted to the learning load according to the learning speed of students. This research method was carried out by filling out a questionnaire by SKS students, which aims to obtain a comprehensive picture of the symbolic interaction of students in Cirebon. The subject of this study was only one person because the researcher had difficulty getting relations from SKS high school students, who had graduated. The implementation of SKS can have an impact on interactions between students. This is due to the difference in the system between SKS classes and regular classes. In SKS classes, students must be accustomed to fast and dense learning so that the time used to interact with other friends is less. The results obtained show that SKS class teaching can help students advance and consider every step they take. Even the existence of SKS classes does not make students individualistic, but rather individuals who are easy to get along with and enjoy working together.